VD_FINDINFO Jug / 2017 / 122 vom 21. September 2016 - VD Tribunal cantonal (2016)
CONSTATATION DES FAITS, ESCROQUERIE, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, INTENTION | 12 CP, 146 CP, 47 CP, 10 CPP (CH), 3 al. 2 let. c CPP (CH), 398 al. 3 let. b CPP (CH)